Wyburn Mason Syndrome: Novel presentation with Bilateral Retinal Arteriovenous malformation - Arora, Deepesh; Gupta, Kanika; Kumar, Yogesh; Sharma, Dinesh (Journal of Ophthalmology and Research, 2020)
A five-year-old girl with poor vision on examination and left eye esotropia was found to have bilateral intraorbital and unilateral intracranial arteriovenous malformation (AVM) and unilateral optic neuropathy. Magnetic Resonance Imaging with contrast revealed a small AVM involving the left ophthalmic artery and a large AVM involving the junction of anterior cerebral artery and anterior communicating artery. The simultaneous presence of retinal and intracranial AVM constitutes the Wyburn- Mason Syndrome (Retinoencephaloangiomatosis). Wyburn mason syndrome is associated with unilateral retinal racemose hemangioma with few cases with bilateral symmetrical involvement been reported in the literature. The present case has asymmetric bilateral retinal AVM and optic neuropathy, rare presentation of rare disease.